Incoherent scatter radar plasma density measurements at Jicamarca using a transverse-mode differential-phase method - Kudeki, Erhan (2003)
The 50 MHz Jicamarca incoherent scatter radar can be used to make very high precision F-region plasma drift measurements with less than a m/s uncertainty and 5 min/ 15 km time/height resolutions. In such measurements the transmitting antenna beam is pointed perpendicular to the geomagnetic field ~ B [e.g., Kudeki et al. , 1999] and backscattered fields consist of magneto-ionic O- and X- components with unequal phase retardations. Detecting the fields with an orthogonal pair of linear-polarized antennas and fitting the average power and differential- phase of the antenna outputs to an appropriate data model we have succeeded in making F-region electron density measurements with data collected during Jicamarca drifts experiments. This procedure provides Jicamarca with a new capability for simultaneous drifts and density measurements at F-region heights.